Q. 285.0( 1 Vote )

# Factorize(i) 9x2 – y2(ii) (3 – x)2 – 36x2(iii) (2x – 3y)2 – (3y + 4y)2(iv) 16x4 – y4

(i) 9x2 – y2 = (3x)2 – (y)2
= (3x + y)(3x – y)

(ii) (3 – x)2 – 36x2 = (3 – x)2 – (6x)2

= (3 - x + 6x) (3 - x - 6x)
= (3 + 5x)(3 – 7x)

(iii) (2x – 3y)2 – (3x + 4y)2 = (2x – 3y + 3x + 4y)(2x – 3y – 3x – 4y)
= (5x + y)(- x – 7y)
= -(5x + y) (x + 7y)

(iv) 16x4 – y4 = (4x2)2 – (y2)

= (4x2 + y2)(4x2 –y2)
= (4x2 + y2)(2x + y) (2x - y)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Polynomials29 mins
Polynomials - Zero to Hero42 mins
Genius Quiz | Polynomials40 mins
Zeros and Degrees of a Polynomial41 mins
Genius Quiz | Division of Algebraic Expressions37 mins
Introduction to Polynomials37 mins
Quiz | Imp. Qs. on Algebraic Identities65 mins
Basic understanding of Polynomials37 mins
Methods to find zeroes of a Polynomial-246 mins
Remainder Theorem and Factor Theorem38 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses